Pengaruh Psikoterapi Positif Terhadap Peningkatan Kesejahteraan Subjektif pada Wanita Dewasa Awal yang Belum Memiliki Pasangan - Catur Pamungkas; Nurul Wardhani; Ahmad Gimmy Prathama Siswadi (JIP (Jurnal Intervensi Psikologi), 2017)
This study aims to determine the effect of positive psychotherapy on improving the welfare well-being of early adult women who do not have a partner/boy friend/fiancee. Positive psychotherapy (PPT) is a therapy developed by Tayyab Rashid using a positive psychological approach. The goal of this therapy is to build a pleasant life, engagement life, and a meaningful life, by optimizing the power side of a person and maximizing the usefulness of positive emotions. The researchs design in this research is quasi experimental, involving two Participants using purposive sampling technique. Data were obtained by using interview method, observation, and questionnaire. The questionnaire used in this research is Satisfaction with Life Scale (SWLS) and positive and negative influences affect schedule (PANAS). Positive psychotherapy is given as much as six sessions. Measurements are made twice, ie before and after the intervention. Data were analyzed using descriptive-qualitative analysis. The results showed. Positive psychotherapy gives effect in improving subjective wellbeing of single early adult women who do not have a partner/boy friend/fiancee.Keywords: positive psychotherapy, positive psychology, subjective well-being